Comparative Study in Zakat Management between Pusat Zakat Sabah and Badan Amil Zakat DIY - Maulana Ihsan Fairi (Department of Islamic Economics, Islamic University of Indonesia, 2020)
Zakat is one of the basic principles that can be used as an instrument to reduce poverty and help Muslims in need. However, the participation of Muslims in Indonesia to paying zakat is still very less, in 2015 only IDR 2.477.457.839.898 which is collected from 207.176.162 Muslim population. Compared with Malaysia in 2015 collected more than MYR 2.334.010.085 or equivalent to IDR 7.002.030.257.000 of 17.375 million Muslim population. It makes this research aim to know the difference between zakat management in Indonesia and Malaysia. To compare it is selected Pusat Zakat Sabah (MUIS) with total collection in 2015 as much as MYR 795.695,17 or equivalent IDR 219.939.753.999 and Badan Amil Zakat DIY with total accumulation in 2015 amounting to IDR 680.990.478. Both are equivalent as zakat institutions at the provincial level. With descriptive qualitative method, it is used to describe data related to zakat management in PZS and Baznas DIY which have been collected. From the descriptive analysis, PZS has advantages in terms of collection and distribution, with the amount of funds collected and the absorption of fund distribution is always exhausted. Then in terms of utilization and Supervision of PZS and Baznas DIY have their respective advantages.